(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2016)
The healthcare industry has historically faced challenges in the transmission of medical records from one facility to another due to privacy concerns and the apprehension that others may exploit the exchange of information. Nevertheless, this is evolving. Health care organizations are unable to obtain long-term patient information as a result of inconsistent policies and permissions that have been granted. The ability to exchange electronic health records will enhance the accuracy of diagnostics when it comes to identifying medical conditions. In order to enhance patient data security and prevent the loss or manipulation of medical records, this system is advised to implement blockchain technology. This survey aims to gain a deeper understanding of the technology’s functionality and potential applications in the healthcare sector, specifically the concept of mining and smart contracts. Block chain technology is a secure method of sharing and preserving medical records with other organizations, ensuring that they are not tampered with.